ANALISIS YURIDIS UNDANG-UNDANG NOMOR 30 TAHUN 1999 TERHADAP PENYELESAIAN SENGKETA KREDIT PERBANKAN DI BIDANG KEPEMILIKAN RUMAH - debora br situmeang, erni (LPPM Universitas Putera Batam, 2023)
Home Ownership Credit, known as KPR, is a banking product in credit, which is currently still regulated in Regulation Number 10 of 1998 concerning Changes to Regulation Number 7 of 1992 concerning Banking or alluded to as the Financial Regulation. In granting housing loans, creditors also sometimes find problems that there are debtors who default, resulting in bad credit. The targets of this study are: To start with, to figure out the gatherings who have privileges and commitments in the House purchasing Credit Arrangement at Bank Maybank Batam; Second, to figure out the reasons for terrible credit on contracts at Bank Maybank Batam, Third, to figure out ways of settling awful advances on contracts utilized by Bank Maybank Batam. The examination technique that specialists use in this kind of exploration is experimental juridical. The data collection technique used was in the form of direct interviews with informants from the Maybank Bank Batam Main Branch Office located in Jodoh. Furthermore, to complete the information from the informants, the researchers asked customers to provide answers to the questions given in the form of questionnaires. The research results that can be described in this paper are: First, the parties who make credit are called: debtors and creditors and they also have rights and obligations; Second, the occurrence of bad credit experienced by Bank Maybank Batam can be seen based on 2 (two) factors, namely: a. the internal factor that causes bad credit is the weak credit administration and supervisory system, b. weak bad credit information system. In addition, external factors that cause bad credit are disappointment of the indebted person's business, debacle for the debt holder or the borrower's business activities in credit settlement. Keywords : Banks; Credit agreement; House; Ownership Credit.